Keanekaragaman dan Kelimpahan Bintang Laut Di Daerah Pesisir Dusun Pandanan, Kecamatan Sekotong Barat, Kabupaten Lombok Barat - Nursakinah, Nursakinah; Rahman, Ibadur; Buhari, Nurliah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Sea stars have morphological characteristics that are radially symmetrical, have 5 (five) or more arms, do not have a skeleton and move freely using tube legs. Sea stars not only function as litter cleaners in the waters, but are also utilized as food processing and handicraft materials. The study aimed to determine the diversity and abundance of sea star species in the coastal area of Pandanan Hamlet, West Sekotong, West Lombok Regency. This study used the belt transect method. All starfish found in the transect recorded the type, number, and habitat characteristics. The results found 6 species of starfish from 4 families namely Echinasteridae, Archasteridae, Ophidiasteridae, and Oreasteridae. The six species are Henricia sp., Archaster typicus, Linckia laevigata, Culcita sp., and Pentaceraster sp. The diversity index (H') has a value of 0.3 - 1.7, the uniformity index (E) is 0.5 - 0.9, and the dominance index (C) ranges from 0.2 - 0.8. The highest abundance in the species Linckia laevigata with a value of 571 ind/ha (station 1) and 333 ind/ha (station 1), while the lowest abundance in the species Pentaceraster sp. 33 ind/ha. All starfish were found to be associated with seagrass plants except Pentaceraster sp.